PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD ( STUDENT TEAMS ACHIEVEMENT DIVISION ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV Di SD NEGERI 008 SUNGAI SEGAJAH KECAMATAN KUBU - Fitri Kunayah; Zulkifli '; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Background research isthe process of teaching and learning is stilldominated by the fourth grade teachers so that students become passive, as wellas materials provided by the teacher and the learning results are not satisfactorywith average scores below the KKM. This study bertjuan to determine whetherthere is influence STAD cooperative learning, both individually and classicerdapat fourth grade student learning outcomes in social studies in theelementary school of 008 Segajah Kcamatan Kubu River. This study wasconducted on 28 students. This data is collected through observation to the dataSTAD cooperative learning model via tail UAS I and UASII for learning outcomesdata. Increased student learning outcomes in the first cycle compared to previousactions performed before PTK. As for the improvement of learning outcomes thatoccur before and after a cycle of PTK diadakam I. From the results of this studyand discussion as it has been described above that the use of STAD cooperativepembbelajaran models are correct then the activities and learning outcomes beincreased, and better. This information proved that the hypothesis which says: theapplication of STAD koopertaif approach can improve the results of the fourthgrade social studiesKeywords: Cooperative Type STAD, Learning Outcomes Of Social Science